2015
DOI: 10.1097/shk.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time on Fluid Resuscitation with Hypertonic Saline (NaCl 7.5%) in Rats with LPS-Induced Acute Lung Injury

Abstract: Acute lung injury (ALI) is a common complication associated with septic shock that directly influences the prognosis of sepsis patients. Currently, one of the main supportive treatment modalities for septic shock is fluid resuscitation. The use of hypertonic saline (HS: 7.5% NaCl) for fluid resuscitation has been described as a promising therapy in experimental models of sepsis-induced ALI, but it has failed to produce similar results in clinical practice. Thus, we compared experimental timing versus clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Hypertonic solution acts on polymorphonuclear A2 adenosine receptors and causes a feedback mechanism that stimulates cAMP and PKA release, thus blocking neutrophil activation [ 41 , 42 ]. Nevertheless, the therapeutic window for a beneficial effect of fluid resuscitation with hypertonic fluid seemed to be very narrow [ 43 ] and may be related to leukocyte activation at the time of fluid use [ 44 ]. Our study confirms the beneficial impact of hypertonic solutions on the IL-6 release but not on TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic solution acts on polymorphonuclear A2 adenosine receptors and causes a feedback mechanism that stimulates cAMP and PKA release, thus blocking neutrophil activation [ 41 , 42 ]. Nevertheless, the therapeutic window for a beneficial effect of fluid resuscitation with hypertonic fluid seemed to be very narrow [ 43 ] and may be related to leukocyte activation at the time of fluid use [ 44 ]. Our study confirms the beneficial impact of hypertonic solutions on the IL-6 release but not on TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation showed an increase in inflammatory markers and histological lesion scores when the infusion of hypertonic saline was made 90 minutes after the induction of endotoxemia, when compared to that performed 15 minutes later 15 , including levels of IL-10. In our study, the levels of IL-10 and INF-gamma showed no significance between therapeutic groups, with all of them being significant lower than IO group, perhaps again influenced by the time of resuscitation and sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with hypertonic sodium chloride solution revealed a prompt blood pressure restoration in experimental severe hemorrhagic shock [812]. Hypertonic solution treatment was effective in reducing mortality rate of endotoxemic rats [13], as well as prevented lung injury by LPS in the experimental model of ARDS [14, 15]. Hypertonic solution has been used in sepsis’ experimental studies and in small clinical studies [9, 16, 17].…”
Section: Introductionmentioning
confidence: 99%